Redução dos danos provocados por Euschistus heros (Fabricius 1798) (Hemiptera: Pentatomidae) na cultura da soja com diferentes inseticidas e doses - Fernandes, Vinicius Kunz (2021)
After soybean cultivation expanded to most of Brazil, mainly in warmer regions, the Stink Bug ended up becoming a key pest of the crop, representing great importance and requiring several researches on integrated pest control methods. The objective of this work was to evaluate the efficiency of insecticides on Euschistus heros. The experiment was carried out in the 2020/2021 crop year under field conditions in the experimental area of CEDEP Agro, in the municipality of Dois Vizinhos, Paraná. The experimental design used was a randomized block design, with 7 treatments using 3 insecticides: Lambda-cyhalothrin + Thiamethoxan, Lambda-cyhalothrin + Dinotefuran and Lambda-cyhalothrin + Sulfoxaflor distributed in 2 different dosages and 4 replications. The number of young and adult stink bugs were evaluated in 2, 5 and 7 days after the first and second application of insecticides in which the products showed significant control of insects and superior in relation to the control, the quality of the seeds after harvest was also verified. where all treatments that contained these insecticides showed higher seed quality compared to the control. The population of Euschistus heros was constant throughout the experiment, remaining close to the control level, while the control showed a population increase well above the average of the treatments..